Disentangling drivers of vertebrate roadkill in a protected area in the Amazon rainforest - Coeli Gomes de Lucena Costa, Andréa; Campos Gomides, Samuel (Austral ecology, 2024)
Vertebrates' roadkill impacts many species in natural areas. However, data on this topic in the Amazon domain are still scarce, especially within protected areas. In this study, we analysed data from 2 years of monitoring amphibians, reptiles, mammals and birds' roadkill on five types of terrestrial transport infrastructure in a protected area in the Brazilian Amazon. We tested which vertebrate classes and feeding guilds were most recorded, the influence of seasonality and the spatial pattern of roadkill. In the studied area, 2795 roadkills were recorded, with amphibians suffering the most casualties. Most of the roadkills occurred during the rainy season (57%). Correcting the roadkill data using observer efficiency and carcass persistence time data, we concluded that mortality rates might be underestimated by up to 40 times when compared to raw data. There was no significant difference between feeding guilds concerning the number of fatalities, and rainfall and temperature significantly affected the roadkill pattern of all vertebrate classes. The spatial pattern of roadkill varied between traffic routes and vertebrate class types. The results indicate that amphibians are the most common victims of roadkill, although they are neglected in many roadkill monitoring. Consequently, mitigation strategies should prioritize periods with the highest mortality rates, as rainfall and temperature influence the frequency of these accidents. In addition, different classes of vertebrates have different patterns of impact concentration along traffic routes, which makes mitigation planning more complex. Therefore, planning to reduce vertebrate deaths from roadkill must consider each taxon's particularity and seasonality.